Chemical Chaperone of Endoplasmic Reticulum Stress Inhibits Epithelial-Mesenchymal Transition Induced by TGF-β1 in Airway Epithelium via the c-Src Pathway - Heung-Man Lee; Ju-Hyung Kang; Jae-Min Shin; Seoung-Ae Lee; Il-Ho Park (Mediators of Inflammation)
Epithelial-mesenchymal transition (EMT) is a biological process that allows epithelial cells to assume a mesenchymal cell phenotype. EMT is considered as a therapeutic target for several persistent inflammatory airway diseases related to tissue remodeling. Herein, we investigated the role of endoplasmic reticulum (ER) stress and c-Src in TGF-β1-induced EMT. A549 cells, primary nasal epithelial cells (PNECs), and inferior nasal turbinate organ cultures were exposed to 4-phenylbutylic acid (4PBA) or PP2 and then stimulated with TGF-β1. We found that E-cadherin, vimentin, fibronectin, and α-SMA expression was increased in nasal polyps compared to inferior turbinates. TGF-β1 increased the expression of EMT markers such as E-cadherin, fibronectin, vimentin, and α-SMA and ER stress markers (XBP-1s and GRP78), an effect that was blocked by PBA or PP2 treatment. 4-PBA and PP2 also blocked the effect of TGF-β1 on migration of A549 cells and suppressed TGF-β1-induced expression of EMT markers in PNECs and organ cultures of inferior turbinate. In conclusion, we demonstrated that 4PBA inhibits TGF-β1-induced EMT via the c-Src pathway in A549 cells, PNECs, and inferior turbinate organ cultures. These results suggest an important role for ER stress and a diverse role for TGF-β1 in upper airway chronic inflammatory disease such as CRS.